PEMBERIAN UPAH PEKERJA DITINJAU DARI UPAH MINIMUM KABUPATEN DAN HUKUM EKONOMI ISLAM - Sari, Septi Wulan (Ahkam: Jurnal Hukum Islam, 2016)
Waging system becomes a complex problem between the employers and the workers whose bargaining position is always weak. To protect the workers’ rights, the government has set up the regional minimum wage. As a matter of fact, this regulation has not been well implemented since there are a lot of workers who are paid under the standard. This study is intended to investigate the waging system of home industries at Tanjungsari Village. This study constitutes a case study which employs descriptive qualitative approach. The data are collected through deep interview and field observation and documentation. The data are analyzed using descriptive qualitative method. This study reveals that (1) there are two kinds of waging system: daily and contract, (2) the wage for the skillful workers has meet the waging standard, but the wage for the unskillful workers is still under the standard, and (3) the waging system, in some cases, has not meet the Islamic waging standard in which the wage is given based on fairness, appropriateness, mutual benefit, and on time. Kata kunci: Sistem Pengupahan, Upah Minimum Kabupaten, Hukum Ekonomi